The spatial logic of informal urbanism inventraset assemblages - Dovey, Kim; Recio, Redento B. (Palgrave Macmillan, 2024)
Highly informalized cities of the global South are often portrayed as chaotic and out of control - this book reveals a spatial logic of informal urbanism that is central to the economic life and livelihoods of such cities. 'Inventraset' is a concept that shows how informal street vending, transport and settlement are fundamentally integrated with each other and the more formal city. Street vending and transport provide crucial forms of employment and mobility, while informal settlement is the key source of affordable and adaptable housing. Informal urbanism is not ideal but it is the way such cities work; it is often hidden or camouflaged within the ideal of a clean, green and modern city to which middle-classes and elites aspire. Through comparative studies, with a focus on Manila and Jakarta, the book maps and analyzes how such cities work through alliances and synergies between vending, transport and settlement - inventraset assemblages are inventive and transgressive, yet settled